Comunicação em rede para a mudança ambiental: as narrativas da sustentabilidade dos institutos de permacultura brasileiros - Foletto, Laura Roratto (2023)
This thesis seeks to understand how the network communication of permaculture institutes, based on representations of sustainability present in their narratives on digital media on the internet, can contribute to environmental change. To do this, we developed an internet ethnography (HINE, 2017), combining various methodological procedures, such as participant observation, case studies, and interviews. The theoretical framework starts from an understanding of consumer society (SLATER, 2002) and environmental sustainability (SACHS, 2008; 2009). We seek to understand the culture of consumption and the unsustainability of capitalism as processes whose logic permaculture institutes seek to subvert, aligning their purposes with environmental sustainability. Furthermore, we seek to understand the uses and appropriations (MARTÍN-BARBERO, 2004; 2009) that these social actors make of the internet to communicate representations of sustainability for environmental change, investigating how networks contribute to this environmental change that permaculture institutes aim to achieve and to what extent it is associated with sustainable development (SACHS, 2008; 2009), in other words, communication for socio-environmental change (TUFTE, 2013; 2015; 2017). We understand the importance that the network communication developed by the institutes has for local environmental change; therefore, their representations on the internet about sustainability contribute to their ability to communicate their socio-environmental actions and practices. Finally, faced with the environmental crisis that plagues the world and the capitalist mode of production and consumption and its discourse of sustainable development, alternatives based on social, economic, cultural, political, and communication dimensions are necessary for significant changes in the environment, as proposed by the institutes. Furthermore, thinking about communication for change based on environmental issues is something new for the field of communication and needs to be researched. Therefore, the institutes promote bottom-up environmental change, that is, local environmental change, even though they aim for transformation based on their practices and positions, they cannot achieve it.